Neu2000 Potentiates a Kainate Response in Mouse Cortical Neurons - Jihyun Noh; Jun-mo Chung (Elsevier, 2013)
Neu2000, acting as an antioxidant with N-methyl-d-aspartate-receptor antagonism, demonstrates excellent protection against ischemic insults in rodents. In this study, we report that Neu2000 also dramatically enhances the activity of kainate (KA) receptors. Neu2000 noncompetitively and reversibly potentiated KA-evoked responses in a voltage-independent manner, mainly by increasing the open probability of KA receptor channels. Keywords:: kainic acid, voltage-clamp, noise analysis